2022
DOI: 10.3390/jcm11154539
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol: A “Pick and Roll” Team Player in Benign Tumors and Cancer Therapies

Abstract: Research on cancer therapies focuses on processes such as angiogenesis, cell signaling, stemness, metastasis, and drug resistance and inflammation, all of which are influenced by the cellular and molecular microenvironment of the tumor. Different strategies, such as antibodies, small chemicals, hormones, cytokines, and, recently, gene editing techniques, have been tested to reduce the malignancy and generate a harmful microenvironment for the tumor. Few therapeutic agents have shown benefits when administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…[20][21][22] Propranolol (Pro) is a nonselective β-AR inhibitor that has demonstrated clinical efficacy in hypertension, cardiac arrhythmias and myocardial infarction, and is now being used experimentally for cancer immunotherapy. [23,24] However, systematic administration of Pro might have the risk of side effects related to the central nervous and cardiovascular system (e.g., sleep disturbance, agitation, bronchospasm/bronchial hyperreactivity and hypoglycemia). [25] With these findings in mind, we propose to construct a nanocarrier that controllably delivers Pro to permit specific targeting to lymph nodes and TME for minimal systemic adverse effects with maximal immunomodulatory outcomes when combined with cancer vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Propranolol (Pro) is a nonselective β-AR inhibitor that has demonstrated clinical efficacy in hypertension, cardiac arrhythmias and myocardial infarction, and is now being used experimentally for cancer immunotherapy. [23,24] However, systematic administration of Pro might have the risk of side effects related to the central nervous and cardiovascular system (e.g., sleep disturbance, agitation, bronchospasm/bronchial hyperreactivity and hypoglycemia). [25] With these findings in mind, we propose to construct a nanocarrier that controllably delivers Pro to permit specific targeting to lymph nodes and TME for minimal systemic adverse effects with maximal immunomodulatory outcomes when combined with cancer vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate this is due to suppression of the SOX18-MVP-axis in tumor endothelial cells and in turn, tumor angiogenesis. Propranolol is currently being studied as single administration adjuvant therapy or in combination with standard therapies in several clinical trials (57). Statin use was first found associated with improved outcomes in colorectal cancer patients in 2005 (58) and subsequent studies confirmed this observation and extend to post-diagnosis statin use (5964).…”
Section: Discussionmentioning
confidence: 99%
“…This is a beta blocker which has been shown to have anti-cancer effects on various carcinomas [ 48 ]. Interestingly, it is also an effective blocker of neuronal and cardiac VGSCs [ 49 ].…”
Section: Drug Combination Strategiesmentioning
confidence: 99%